KINETICS OF THE TREATMENT OF ORGANIC DYE BASED ON MODIFIED RED MUD - The Anh, Dang; Huy Dinh, Vu; Thi Van Anh, Nguyen; Sy Duc, Dao; Quang Trung, Do (Journal of Forestry Science and Technology, 2017)
In this paper, red mud denatured by Iron (III) sulfate is used for researching decomposition reaction kinetics of Reactive Yellow 160 (RY 160) dye using Heterogeneous Fenton Technique. Basic characteristics of red mud before and after denaturation are determined through scanning electron micrograph (SEM) and Energy Dispersive X-Ray Spectroscopy (EDX). In the appropriate conditions on catalyst content (1.5 g/L), hydrogen peroxide content (2.29 mM), pH = 2, with more than 99.2% of RY 160 dye is eliminated at 30°C with a rate constant of 0.0383 min-1 (R2 = 0.9939); surveying temperature in the range of 30°C - 50°C, the reaction follows first order kinetics with activation energy 31.9 kJ/mol (R2 = 0.9804); surveying catalyst content, the largest rate constant is k = 0.0381 min-1 with catalyst content of 1.5 g/L; surveying hydrogen peroxide content, the largest rate constant is k = 0.0367 min-1 with hydrogen peroxide concentration of 2.29 mM; surveying pH, the largest rate constant is k = 0.0391 min-1 at pH = 2.